How does this increase Pricing and Consumers’ Willingness to Pay in the Art Market? - Cha, Aaron Gun-Hee; Woo, Youngmin (Technium Social Sciences Journal, 2025)
New artists in contemporary art markets, mostly of the Gen-Z generation and Millennials, are significantly challenged in terms of value creation and identification of buyers. They are not established artists and have no historical sales records, customer networks, and therefore struggle to build their market positioning, and thus bring high uncertainty to revenue levels. Customers in this very market are heterogeneous: some consumers care about aesthetics, technical expertise, or a reputation, whereas others are concerned about ethical production, sustainability, or environmental values. This is a combination of both market uncertainty and a variety of consumer intentions that leads to these unstable early income streams. The paper discusses how the term upcycled can be a strategic tool to reduce valuation uncertainty, stabilize prices, and capture consumers with a greater WTP. We used signaling and screening theory to model the decision-making process of an artist who decides whether to create normal artwork or upcycled artwork with an emphasis on buyers who are environmentally conscious. The consumers have been classified into the general and environmentally conscious types, with different WTP distributions. The model takes into consideration production costs, price volatility, and the expected payoffs in order to find the conditions under which the upcycled labeling would maximize the expected utility of the artist.